Study of physiological and biochemical characteristics of pure cultures of lactic acid bacteria (Experimental biology, 2015)
Bacteria synthesize PG hydrolases which are capable of cleaving the covalent bonds of own PG and play an important role in modeling PG, required for bacterial growth and division. The aim of the present work was to study the physiological and biochemical characteristics of pure cultures of lactic acid bacteria isolated from food and microflora of clinically healthy person, on an example of the main PG hydrolases by.
Keywords: Lactic acid bacteria; peptidoglycan hydrolases; substrate specificity; proteolysis; method of renaturing polyacrylamide gel electrophoresis